2015
DOI: 10.1177/1356336x15598789
|View full text |Cite
|
Sign up to set email alerts
|

An examination of Greek physical educators’ implementation and perceptions of Spectrum teaching styles

Abstract: The main purpose of the present study was to examine Greek physical education (PE) teachers' selfreported use of the Spectrum of teaching styles and their perceptions of the benefits of adopting these styles for their students. An additional goal was to explore the teachers' perceived ability to implement these teaching approaches. The participants of the study were 219 (132 males, 87 females) PE teachers. Using an adaptation of Kulinna and Cothran's (2003) Spectrum of teaching styles questionnaire, the PE tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…Previous research reported that the reproduction teaching style is the most common approach and that it is widely used in PE [18][19][20]. Some reproduction teaching styles (e.g., command, and practice) are mainly based on learning by imitation of models of movement, and they are effective when working on complex tasks, cardiorespiratory fitness and/or in conditions presenting high emotional involvement [17,21].…”
mentioning
confidence: 99%
“…Previous research reported that the reproduction teaching style is the most common approach and that it is widely used in PE [18][19][20]. Some reproduction teaching styles (e.g., command, and practice) are mainly based on learning by imitation of models of movement, and they are effective when working on complex tasks, cardiorespiratory fitness and/or in conditions presenting high emotional involvement [17,21].…”
mentioning
confidence: 99%
“…For example, large-scale international comparison surveys (Hardman & Marshall, 2005;Pühse & Gerber, 2005) suggest teachers themselves remain in control of the events that take place in physical education classes. Additionally, large-scale studies researching the styles of teaching favoured by participants (Curtner-Smith et al, 2001;Kulinna & Cothran, 2003;Syrmpas et al, 2016) discovered that teachers prefer to take control of the decisions in regards to what happens before, during, and after the teaching episodes that comprise lessons. Concerns regarding the prevalence of 'direct' teaching have intensified in recent years as the possibility of, and expectations for, physical education lessons to address a wider range of learning experiences have emerged across the Anglophone world (Bailey et al, 2009).…”
Section: Physical Education Teachers' Practices: What Do We Know?mentioning
confidence: 99%
“…Recently, Greek researchers have found that PE teachers (Syrmpas et al, 2016) and preservice PE teachers (Syrmpas and Digelidis, 2014) have reported using spectrum teaching styles from the reproduction cluster more often than those from the production cluster. Similarly, a number of studies in the UK (Curtner-Smith and Hasty, 1997; Curtner-Smith et al, 2001), the USA (Cothran et al, 2000; Kulinna and Cothran, 2003) and Finland (Jaakkola and Watt, 2011) confirmed the preference of using reproduction-based teaching styles in practice.…”
Section: Introductionmentioning
confidence: 99%